2014
DOI: 10.1111/famp.12066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Family Systems Intervention for Managing Pediatric Chronic Illness: Mastering Each New Direction (MEND)

Abstract: Family systems play a crucial, albeit complex, role in pediatric chronic illness. Unfortunately, very few psychosocial interventions are available to help these stressed families navigate the developmental steps of chronic illness. A new intervention (MEND) addresses the needs of these families and applies to a broad range of chronic illnesses. This article presents this family systems intervention as well as includes preliminary program evaluation data on 22 families that graduated from the program. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 37 publications
(71 reference statements)
3
40
0
Order By: Relevance
“…As opposed to psychosocial interventions that focus on one disease type alone, this intervention and study are inclusive of many CIs. Not only does the inclusion of a variety of conditions improve generalizability of our findings, it underscores the commonalities shared by children with CI in terms of both issues and clinical solutions, a key assumption of the MEND intervention (Distelberg et al, 2014). Although we believe this is a significant strength of the MEND program, given the small sample size of this study, we are cautious about the generalizability of results across all disease types.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As opposed to psychosocial interventions that focus on one disease type alone, this intervention and study are inclusive of many CIs. Not only does the inclusion of a variety of conditions improve generalizability of our findings, it underscores the commonalities shared by children with CI in terms of both issues and clinical solutions, a key assumption of the MEND intervention (Distelberg et al, 2014). Although we believe this is a significant strength of the MEND program, given the small sample size of this study, we are cautious about the generalizability of results across all disease types.…”
Section: Discussionmentioning
confidence: 69%
“…Mastering Each New Direction (MEND; Distelberg, Williams-Reade, Tapanes, Montgomery, & Pandit, 2014) is a 21-session/7-week intensive outpatient family therapy-based treatment protocol designed to improve adherence to medical regimens. MEND works to improve functioning across family, social, and health-care systems to positively influence self-management behavior through cognitive, emotional, familial, and social processes.…”
mentioning
confidence: 99%
“…If these pathways are supported empirically, this will support prior work that suggests that to meaningfully impact HRQOL, treatments must incorporate the family system (Distelberg, Williams-Reade, Tapanes, Montgomery, & Pandit, 2014;Drotar, 2013;Wood et al, 2000). Given that depression often exacerbates issues related to both identity formation and adjustment to CI, we anticipated that changes in depression would inversely predict changes in self-concept.…”
mentioning
confidence: 72%
“…By contrast, teens with avoidant attachment styles have been shown to delay seeking treatment even when symptoms warrant it (Maunder & Hunter, 2001). This study is not focused on the overall effectiveness of MEND, as such studies can be found greater detail in other publications (Distelberg et al, 2014(Distelberg et al, , 2017. To evaluate these relationships over time, we analyzed participant data from the Mastering Each New Direction (MEND) program, a 3-month psychosocial, family based intensive outpatient program for adolescents with CI.…”
Section: Parent-child Attachmentmentioning
confidence: 99%
See 1 more Smart Citation